Aesthetic relationship between personality emotions and contemporary graphic design patterns on the surfaces of textiles - Tayyab Naveed; Sidra Batool; Rehana Ilyas; Nadeem Afraz; Ume Sahar; Arooj Shahid; Muhammad Awais (Mehran University Research Journal of Engineering and Technology, 2024)
In this work, five different types of animated graphic design ideas (traditional, 2D, 3D, stop motion, motion) were examined on three different textile fabrics (cotton, silk, polyester) through digital printing. Psychological-emotional expressions (openness, conscientiousness, extroversions, agreeableness, and neuroticism) were investigated that influenced the perceptual criteria. Lastly, a quantitative investigation was carried out from a sample of 300 students whose ages varied from 20 to 24 years old for an analysis of aesthetic appeal through a 5-point Likert scale. The results revealed that motion animation design has the most effective aesthetic appeal while the stop motion design pattern has the least aesthetic appeal. Silk fabric samples have better graphic consequences whereas polyester fabric samples have the least. Moreover, individuals with neuroticism emotional personality have the least effective response while agreeableness has the utmost for the sense of aesthetics. 71% of students were accustomed to aesthetic appeal as compared to structural fabrics.